Pulmonary function changes in asymptomatic smokers - a community survey in Udupi, Karnataka, India - Elumalai, Senthil Kumar; Maiya, Arun G.; Chakravarthy, Kalyan B. (International Journal of Research in Medical Sciences, 2017)
Background: Smoking has been labeled the most important preventable cause of a respiratory disease and its effects in a smoker are well established. A better understanding on the pulmonary function impairments in an asymptomatic smoker is the need of the hour. Objective: To study the pulmonary function changes in asymptomatic smokers and non- smokers and to establish the dose -effect relationship amongst asymptomatic smokers. Methods: A cross sectional survey was conducted in Udupi district of Karnataka, India. 140 men aged between 20 to 45 years with a BMI ranging from 18.5 to 29.9 Kg2 /m was enrolled in to the study. 70 subjects were asymptomatic smokers and the other 70 were non-smokers. Outcomes measured were standard spirometric measures for pulmonary function and symptoms like breathlessness, cough and sputum using a Breathlessness Cough Sputum scale. Results: The mean age (mean ± SD) of non-smokers and asymptomatic smokers enrolled was 34.7±5 and 33.8±5 years respectively. The mean smoking dose amongst the asymptomatic smokers was 15.74±5.5 pack years. FEV1 amongst the asymptomatic smokers showed a negative correlation with smoking dose (p<0.05) and there was a significant difference in FEV1, FVC, PEFR, MVV and FEF 25- 75 % (p<0.001) amongst the asymptomatic smokers and non-smokers. Conclusions: Asymptomatic smokers showed low values of pulmonary function parameters compared to those in non-smokers.